Local recurrence of Ewing sarcoma: Is wide excision an acceptable treatment?. Issue 4 (8th July 2019) - Xue, Ruifeng; Lewis, Valerae O.; Moon, Bryan S.; Lin, Patrick P.
Abstract: Background and Objectives: Local recurrence in Ewing sarcoma (ES) is associated with poor prognosis. The purpose of the study is to determine what factors affect overall survival after local recurrence and whether wide excision constitutes appropriate treatment. Methods: From 1992 to 2017, 26 patients were treated for local recurrence of ES. Sixteen patients presented with local recurrence only while 10 had metastasis. The median follow‐up was 23 months (range, 3‐255 months). Overall survival was assessed with Kaplan–Meier analysis. Results: At the last follow‐up, seven of 26 (27%) patients were alive. Overall survival after local recurrence was 28% at 5 years. Later onset of local recurrence ( P = .041), surgical treatment ( P < .001), and complete eradication of all recurrent disease ( P < .001) predicted better survival. Metastasis was associated with worse survival ( P = .014). All three patients who survived more than 10 years were treated with wide local excision. A second local recurrence developed in seven patients (28%) but did not predict worse overall survival. Conclusions: Overall survival after local recurrence is better for patients with nonmetastatic disease treated surgically. Wide excision can be compatible with long survival. We do not advocate amputation on a routine basis for local recurrence. Complete eradication of all diseases is associated with better survival.